KAJIAN KUDA LUMPING SEBAGAI IDENTITAS BUDAYA JAWA: MENUJU PENGAKUAN INTERNASIONAL SEBAGAI WARISAN BUDAYA TAK BENDA - Br Karo, Aulia Maharani Putri; Raja Gukguk, Devy Meylani; Aprija, Dina; Siburian, Yeremia; Khairi, Nurkhafizah (Studi Budaya Nusantara, 2024)
This research aims to examine the role of kuda lumping as a symbol of Javanese cultural identity and pioneer efforts for its international recognition as an Intangible Cultural Heritage. The lumping horse is a Javanese cultural icon that has become a strong identity for the local community. This performance shows the actions of the dancers as if they were riding horses with agile movements and the accompanying rhythm of gamelan music. Apart from horse riding, kuda lumping also often performs spiritual acts, such as trance, eating broken glass, and stabbing itself with sharp objects. The research method used was descriptive qualitative, with the research subject being the owner of the kuda lumping group and one of its members. Data collection techniques were carried out through observation, interviews and literature study. The research results show that kuda lumping is not only a traditional dance performance, but also a symbol that reflects cultural values, courage and skill. The kuda lumping group is identified as a guardian of cultural heritage that needs to be safeguarded and promoted more widely. These findings strengthen the urgency of international recognition of kuda lumping as an important part of Indonesia's intangible cultural heritage. Recommendations from this research include the need for further support from the government and related institutions to document, preserve and promote Kuda Lumping as an integral part of Java's cultural richness. Concrete steps such as creating digital archives, learning from the younger generation, and participating in international cultural events can increase understanding and appreciation of kuda lumping globally